INCREASING STUDENTS’ VOCABULARY THROUGH APPLICATION OF SOCIAL MEDIA AT SMP GPDI BEREA TONDANO - Ravensky Silamba; Nurmin Samola; Paula Rombepajung (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study is to find out the whether youtube social media increasing students’ vocabulary at GPDI Berea Tondano Junior High School. The subject of the study is Eight Grade Student. The result of this study shows that mean score Post-test (82.75) was higher than mean score Pre-test (32.5). Paired Sample Test showed that the significance value of 0.000, meaning less than 0.05, then Ho was rejected and Ha was accepted. The result means there was a significance difference between before and after treatment. The normality test using the SPSS Program known that 4.20 (>0.05). Based on the result of this study shows increasing students’ vocabulary through application of social media youtube has a big chance and really effective to increase students’ vocabulary.